Familial distal arthrogryposis and elevated serum IgE levels - (:unkn) unknown (My University, 1995)
This case report describes a 3 year old girl with type I distal arthrogryposis, who was admitted twice for staphylococcal abscesses on the abdominal wall. Immunological evaluation was significant only for a moderately elevated serum IgE level (1230 IU/mL). All the members of her family who had type I distal arthrogryposis were also found to have high serum IgE levels, excluding the mother. The patient was given a course of alpha-interferon (IFN-α) therapy which resulted in a marked decline in the serum IgE level before the elective surgery for her arthrogryposis.